2020
DOI: 10.1523/jneurosci.1665-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Born Hippocampal Neurons Undergo Extended Development and Are Morphologically Distinct from Neonatally-Born Neurons

Abstract: During immature stages, adult-born neurons pass through critical periods for survival and plasticity. It is generally assumed that by 2 months of age adult-born neurons are mature and equivalent to the broader neuronal population, raising questions of how they might contribute to hippocampal function in old age when neurogenesis has declined. However, few have examined adult-born neurons beyond the critical period or directly compared them to neurons born in infancy. Here, we used a retrovirus to visualize fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 114 publications
(160 reference statements)
5
57
0
Order By: Relevance
“…Second, as other models of TBI and seizure models result in aberrant migration of adult-born DG neurons (Dashtipour et al, 2003;Emery et al, 2005;Shapiro et al, 2008Shapiro et al, , 2011Murphy et al, 2012;Ibrahim et al, 2016;Ratliff et al, 2020), future work could assess whether the greater number of BrdU+ cells in DG subregions adjacent to the SGZ (hilus and oGCL) means this may also be occurring in our mTBI model. In our study, DCX+ staining in non-neurogenic regions was ambiguous, but future work using transgenic or viral-mediated visualization of DCX+ cells or the neuronal phenotyping mentioned above would be useful in this regard (van Praag et al, 2002;Laplagne et al, 2006;Wood et al, 2011;Kathner-Schaffert et al, 2019;Cole et al, 2020;Tensaouti et al, 2020). Third, it will be important to assess if our mTBI model changes the dendritic morphology of the adult-born DG granule cells as has been reported in other and more severe TBI models (Folkerts et al, 1998;Gao et al, 2011;Villasana et al, 2015;Ibrahim et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…Second, as other models of TBI and seizure models result in aberrant migration of adult-born DG neurons (Dashtipour et al, 2003;Emery et al, 2005;Shapiro et al, 2008Shapiro et al, , 2011Murphy et al, 2012;Ibrahim et al, 2016;Ratliff et al, 2020), future work could assess whether the greater number of BrdU+ cells in DG subregions adjacent to the SGZ (hilus and oGCL) means this may also be occurring in our mTBI model. In our study, DCX+ staining in non-neurogenic regions was ambiguous, but future work using transgenic or viral-mediated visualization of DCX+ cells or the neuronal phenotyping mentioned above would be useful in this regard (van Praag et al, 2002;Laplagne et al, 2006;Wood et al, 2011;Kathner-Schaffert et al, 2019;Cole et al, 2020;Tensaouti et al, 2020). Third, it will be important to assess if our mTBI model changes the dendritic morphology of the adult-born DG granule cells as has been reported in other and more severe TBI models (Folkerts et al, 1998;Gao et al, 2011;Villasana et al, 2015;Ibrahim et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…Second, as other models of TBI and seizure models result in aberrant migration of adult-born DG neurons (Dashtipour et al, 2003; Emery et al, 2005; Shapiro et al, 2008, 2011; Murphy et al, 2012; Ibrahim et al, 2016; Ratliff et al, 2020), future work could assess whether the greater number of BrdU+ cells in DG subregions adjacent to the SGZ (hilus and oGCL) means this may also be occurring in our mTBI model. In our study, DCX+ staining in non-neurogenic regions was ambiguous, but future work using transgenic or viral-mediated visualization of DCX+ cells or the neuronal phenotyping mentioned above would be useful in this regard (van Praag et al, 2002; Laplagne et al, 2006; Wood et al, 2011; Kathner-Schaffert et al, 2019; Cole et al, 2020; Tensaouti et al, 2020). Third, it will be important to assess if our mTBI model changes the dendritic morphology of the adult-born DG granule cells as has been reported in other and more severe TBI models (Folkerts et al, 1998; Gao et al, 2011; Villasana et al, 2015; Ibrahim et al, 2016).…”
Section: Discussionmentioning
confidence: 79%
“…In this study, we specifically analyzed adult newborn neuron integration 1 month after labeling, i.e., shortly after the peak of spine morphogenesis and dendrite growth ( Zhao et al, 2006 ). However, newborn neurons’ spines are constantly generated for at least 2 more months and remain mobile, along with differential synaptic connectivity when compared to fully mature granule cells ( Toni and Sultan, 2011 ; Lemaire et al, 2012 ; Cole et al, 2020 ). Thus, we cannot exclude that the observed effects may become more or less severe at later timpoints.…”
Section: Discussionmentioning
confidence: 99%
“…A recent long-term follow-up of dendritic trees indicated that hippocampal adult newborn neurons tend to acquire one or more additional primary dendrites after several weeks, probably via displacement of the first branch point of the primary dendrite ( Cole et al, 2020 ). Overexpression of A53T α-syn increased the number of primary neurites in rat midbrain neurons ( Koch et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%